2021
DOI: 10.4314/ejst.v14i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of farm level market supply of tomatoes in Fogera district, South Gondar Zone of the Amhara Region, Ethiopia

Abstract: This research attempted to analyze the determinants of market supply of tomato in Fogera district, South Gondar zone, Amhara Region of Ethiopia. Tomatoes generate income for the poor farmers of Ethiopia. Primary and secondary data were collected. The primary data was generated though a household survey (N=235), a pre-tested structured questionnaire and a key informant interview using a checklist. The data were analyzed using multiple linear regression model. The model results showed livestock ownership, size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…u i is the stochastic error term. The regression equation (9) shows a linear relationship between dependent variable and explanatory variables and the equation is estimated using OLS method. The explanatory variables that are used in the regression are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…u i is the stochastic error term. The regression equation (9) shows a linear relationship between dependent variable and explanatory variables and the equation is estimated using OLS method. The explanatory variables that are used in the regression are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…According to Wondim (2021), vegetable production including tomato is becoming an increasingly important activity in the agricultural sector of Ethiopia following the development of irrigation and increased emphases given by the government to small scale commercial farmers. According to Kassaw et al (2019), vegetables are important for income generation to a large proportion of the rural households. Enhancing tomato farmers to reach markets and actively engage in the markets is a key challenge influencing tomato production in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that access to credit had the highest magnitude of marginal effects from their regression result, implying that it was an important determinant of crop production. Kassaw et al [92] found that credit increased tomato supply in Ethiopia, while Onyeneke et al [45] found that credit increased cassava, maize, and rice production in the long run in Nigeria. From a policy view point, credit creates a better outcome in agricultural production.…”
Section: Discussionmentioning
confidence: 99%